2016
DOI: 10.1109/tbme.2015.2511581
|View full text |Cite
|
Sign up to set email alerts
|

Modulated-Alignment Dual-Axis (MAD) Confocal Microscopy Optimized for Speed and Contrast

Abstract: Modulated-alignment dual-axis (MAD) confocal microscopy combines the benefits of dual-axis confocal (DAC) microscopy and focal-modulation microscopy (FMM) for rejecting out-of-focus and multiply scattered light in tissues. The DAC architecture, which utilizes off-axis and separated beam paths for illumination and detection, has previously been shown to be superior to single-axis confocal (SAC) microscopy for the spatial filtering (rejection) of unwanted background light. With the MAD approach, a modulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…One of the challenges for laser‐scanning microscopy of biological tissues is that refractive heterogeneities due to micro‐architectural structures – such as nuclei, organelles, glands, and vasculature – can cause spatial variations of optical beam foci in terms of shape (aberrations/distortions) and position (beam steering) . In particular, the tissue‐imaging performance of a DAC microscope is highly sensitive to the effects of refractive heterogeneities because of its reliance on two beam paths (illumination and collection) that must intersect at their foci . For example, it has been shown that the in‐focus signal collected by a DAC microscope is significantly decreased when the alignment of the illumination and collection beams is spatially modulated at the micron scale .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges for laser‐scanning microscopy of biological tissues is that refractive heterogeneities due to micro‐architectural structures – such as nuclei, organelles, glands, and vasculature – can cause spatial variations of optical beam foci in terms of shape (aberrations/distortions) and position (beam steering) . In particular, the tissue‐imaging performance of a DAC microscope is highly sensitive to the effects of refractive heterogeneities because of its reliance on two beam paths (illumination and collection) that must intersect at their foci . For example, it has been shown that the in‐focus signal collected by a DAC microscope is significantly decreased when the alignment of the illumination and collection beams is spatially modulated at the micron scale .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the tissue‐imaging performance of a DAC microscope is highly sensitive to the effects of refractive heterogeneities because of its reliance on two beam paths (illumination and collection) that must intersect at their foci . For example, it has been shown that the in‐focus signal collected by a DAC microscope is significantly decreased when the alignment of the illumination and collection beams is spatially modulated at the micron scale . In addition, as shown in previous studies with tissue phantoms and through in vivo imaging experiments of human epidermis, refractive heterogeneities in tissues lead to a degradation in spatial resolution for DAC microscopy , with a concomitant loss in sensitivity (signal‐to‐noise ratio, SNR) and contrast (signal‐to‐background ratio, SBR).…”
Section: Introductionmentioning
confidence: 99%